2000
DOI: 10.1093/occmed/50.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Does Vacation Enable Recuperation? Changes in Well-being Associated with Time Away from Work

Abstract: The objective of this paper was to study the change of well-being associated with vacation and the effect of vacation related variables on these changes. Fifty-three employees (16 women, 37 men) of a medium sized aluminium hardware manufacturer in Austria participated. Measures were taken 10 days before and 3 days after vacation. A small follow-up group at 5 weeks post-vacation was included. Three days after vacation, physical complaints, the quality of sleep and mood had improved as compared to before vacatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 19 publications
2
86
0
3
Order By: Relevance
“…However, surprisingly few studies have investigated the potentially recovering impact of vacation. Insofar as evidence is available, it shows that immediately after vacation, recovery indicators (eg, fatigue, sleep quality, health complaints) had improved when compared with the levels before vacation but that the gains from vacations faded within a couple of weeks after work was resumed (54)(55)(56)(57). The scarce respite research addressing the impact of specific vacation activities reveals findings that are similar to the pattern of results emerging for activities during shorter periods of respite from work.…”
Section: Recovery In the Context Of Work And Nonworkmentioning
confidence: 76%
“…However, surprisingly few studies have investigated the potentially recovering impact of vacation. Insofar as evidence is available, it shows that immediately after vacation, recovery indicators (eg, fatigue, sleep quality, health complaints) had improved when compared with the levels before vacation but that the gains from vacations faded within a couple of weeks after work was resumed (54)(55)(56)(57). The scarce respite research addressing the impact of specific vacation activities reveals findings that are similar to the pattern of results emerging for activities during shorter periods of respite from work.…”
Section: Recovery In the Context Of Work And Nonworkmentioning
confidence: 76%
“…The first 3 authors of the present article studied the remaining 11 papers and excluded 4 more papers. In 2 cases, papers were written by the same authors [12][13][14][15] , based on the same sample with the second paper not offering extra information for our research purposes. Therefore the second paper was excluded in both cases 13,15) .…”
Section: Methodsmentioning
confidence: 99%
“…Attrition from the pre-vacation to the first post-vacation measurement varied between 5% 20) and 59% 12) . The loss of participants from the prevacation to the post-vacation 2 measure varied between 5% 20) and 86% 12) . Sex, age and occupation: The distributions of sex, age and occupation were diverse in the reviewed studies.…”
Section: Sample and Design Characteristicsmentioning
confidence: 99%
“…A number of pre-test/post-test design studies have found higher levels of happiness (Gilbert and Abdullah 2004;) and other positive effects, such as decreased levels of stress and generally better health, after a holiday trip (Strauss-Blasche et al 2000;Westman and Eden 1997;Westman and Etzion 2001), although these effects fade out rather quickly (De Bloom et al 2009). …”
Section: Earlier Research On Tourism and Happinessmentioning
confidence: 99%